PENGARUH PROFITABILITAS, KOMITE AUDIT, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP AUDIT DELAY - Wirnawati, Farah; Zakaria, Adam; Nasution, Hafifah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This purpose of this study is to determine the effect of profitability, audit committee, and prior year audit opinion to audit delay of properties and real estate company on IDX for the period 2020-2021. The type of this study is quantitative, and the data used is secondary data. The sample used in this study were 65 companies with number of total of 130 observational data obtained using purposive sampling technique. The analytical method used is a multiple linear regression analysis and used the statistical software is IBM SPSS version 20. Based on the result of this study, its shown that (1) profitability has a negative effect on audit delay, (2) auditee committee has no significant effect on audit delay and (3) prior year audit opinion has no significant effect on audit delay